Alpha-Lipoic Acid Treatment Reduces the Levels of Advanced End Glycation Products in Type 2 Diabetes Patients with Neuropathy - Sára Csiha; Marcell Hernyák; Ágnes Molnár; Hajnalka Lőrincz; Mónika Katkó; György Paragh; Miklós Bodor; Mariann Harangi; Ferenc Sztanek; Eszter Berta (Biomedicines, 2025)
Background/Objectives: Type 2 diabetes mellitus (T2DM) and its macro- and microvascular complications are major health concerns with multiple factors, like advanced end glycation products (AGEs), in the background. AGEs induce long-lasting functional modification of the proteins and collagen in the vascular wall and nerve tissue. We investigated the effect of alpha-lipoic acid (ALA) treatment on AGEs, soluble AGE receptor (sRAGE), the AGE/sRAGE ratio, and the parameters of endothelial dysfunction and their correlations. Methods: In our 6-month intervention study, 54 T2DM patients with neuropathy treated according to the actual therapeutic guidelines with unchanged oral antidiabetic drugs were included and treated by daily oral administration of 600 mg ALA. A total of 24 gender and age-matched T2DM patients without neuropathy served as controls. Results: In our work, we first demonstrated the attenuating effect of alpha lipoic acid therapy on AGEs in humans (11.89 (9.44–12.88) to 10.95 (9.81–12.82) AU/μg (p = 0.017)). sRAGE levels or the AGEs/sRAGE ratio were not affected by ALA treatment or by the presence of neuropathy. We found a correlation between the changes of AGEs and the improvement of current perception threshold and progranulin levels, and an inverse correlation with the change of asymmetric dimethylarginine. Conclusions: According to our results, ALA decreases AGEs, which may contribute to the clinically well-known beneficial effect in diabetic neuropathy and improvement of endothelial function.